Integrated Model of Balanced Score Card and Technology Component Measurement: A Strategic Perspective in Indonesia Biofuel Engineering Development - Sukardi, Sukardi; Nasution, Arman Hakim (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
The development of biofuel as an ecofriendly energy alternative has a value chain problem in alignment policies between related parties. Identifiying its alignment, we make a strategic mapping by building integrated base scorecard, so the strategic target in the subsequent perspective layer can be developed more realistically. Structural Equation Modeling (SEM) modeling was used to examine horizontal connection validity to show strong relation between objectives strategy, and it will be measured of constructed component on the internal process by Technology Coefficient Contribution indexes.